Circuit Modeling and Signal Transmission Analysis of Inductive Coupler in Wired Drill Pipe. (27th March 2021) - Jia, Jia; Su, Yinao; Shen, Yue; Wang, Long; Zhang, Lingtan; Ling, Yan
Abstract : The telemetry drill string transmits the measured drilling and formation parameters near the bit to the ground at high speed through the transmission line in the wired drill pipe and the inductive coupler formed by the coil embedded in the drill pipe joint. The voltage transfer function of the inductive coupler seriously affects the signal transmission characteristics of the telemetry drill string. Present research methods cannot accurately and quantitatively describe the influence of the electromagnetic parameters of the inductive coupler on its voltage transfer function. This paper quantitatively analyzes the effects of the electromagnetic parameters of the inductive coupler on signal transmission through reasonable high-frequency circuit modeling. The generation mechanism of eddy current in the magnetic core and the interaction mechanism between eddy current and coupling coils are studied using the electromagnetic detection analysis method of nondestructive testing (NDT) technology. Then, the high-frequency circuit model of the coupler containing eddy current loss is established. The mathematical model of input impedance and signal transmission characteristics of the inductive coupler is established through circuit analysis. The influence of the electromagnetic parameters of the magnetic core and the load resistance of the coupler on the voltage transmission characteristics and power transmission characteristics of the coupler is studied. The research results show that the relative permeability of the magnetic core, load resistance of the coupler, and signal frequency seriously affect the signal voltage transmission. When the relative permeability of the magnetic core material reaches 50, the voltage transmission of the inductive coupler is effectively improved. The electromagnetic simulation results are consistent with the theoretical analysis of the circuit model, which proves the correctness of the circuit model. This paper provides theoretical guidance for the electromagnetic design of inductive couplers and the improvement of signal transmission characteristics of telemetry drill string.